Maintaining Health with Jamu: The Role of DPC ASPETRI Magetan in Supporting the Health of Public Transport Users at Maospati Terminal - Wibowo, Teguh Setiawan; Sulistyowati, Ririk Catur; Yulis, Sari; Saimun, Saimun; Winarti, Winarti (Eastasouth Institute, 2025)
The community service activity organized by the Regional Executive Board of the Indonesian Traditional Herbal Practitioners Association (DPC ASPETRI) Magetan was held on March 29, 2025, at Maospati Terminal as a tangible contribution to public health support through traditional approaches. In this event, a total of 100 bottles of fresh herbal drinks made from butterfly pea flower and lemon were distributed to terminal visitors. Without any accompanying educational session, the activity was purely aimed at providing direct benefits to the public. The choice of natural ingredients with antioxidant and body-refreshing properties added value in supporting the vitality of people on the move. Led by the Chairwoman of DPC ASPETRI Magetan, Mrs. Ririk Catur Sulistyowati, along with three board members, this initiative created a positive social impact, particularly in improving public access to safe and convenient traditional health products. This herbal distribution demonstrated how a simple yet targeted approach could directly enhance the quality of life in the community.